Desmoplastic Fibroma and Cemento Ossifying Fibroma of The Anterior Maxilla: A Rare Case Report: Desmoplastic Fibroma dan Cemento Ossifying Fibroma: Laporan Kasus Langka - Victor Pakpahan; Eky Nasuri; Vera Julia (Dentika: Dental Journal, 2021)
Tumors located in the maxillofacial part of the body were classified by WHO in 2017 and among these are intraosseous form of fibromatosis known as Desmoplastic and Cemento-ossifying fibromas. These tumors usually occur in the head and neck region, especially in the mandible and are relatively rare in the maxilla. Meanwhile, this study aims to discribe a rare case of the cemento ossifying fibroma that had been previously diagnosed as desmoplastic fibroma with a mass tumor in the anterior of the maxilla. A 22 years old female reported to the Cipto Mangkusumo Hospital with the main complaint of a lump in the right side of the upper jaw which appeared 2 years prior to the operation. In April 2017, the patient had a biopsy in Tarakan Hospital and the result was a desmoplastic fibroma. Due to the lump enlargement, the patient was admitted to RSCM in July 2019 and had biopsy incision with a diagnosis of cemento ossifying fibroma which was confirmed by the histopathological examination and histology report. The resection of the right part of maxilla was conducted alongside with reconstruction using the free fibular flap. Moreover, cemento ossifying fibroma and desmoplastic fibroma shared similar features, namely, clinical, histological and radiological features which are important in establishing the diagnosis and treatment of patient. Hence, extensive enucleation or resection is required due to the progressive nature of the tumor to prevent the potential for further recurrences.